The role of organizational culture in improving the performance of employees in the institutions - Ferroum, Safia; Kaouan, Mouhamed (Journal of Human Sciences, 2021)
Contemporary organizations witness countless conflicts and problems that threaten their very being, and this is mainly due to the rapid evolution and changes that the world undergoes; especially the ones related to work and workers. What we see nowadays as the strength and management competency in addition to labor force in companies’ management has the most distinguished impact on its thriving and growth. Moreover, the challenges imposed by this dynamic movement forces administrations, be it private or state administrations, to adopt, from time to time, numerous procedures to update their programs in order to manage the different situations effectively; especially when it comes to its culture, that represents the main pillar and the reference to all behaviors emerging from the single organism; which on its own can cripple its development or increase the yield of their employees and adjust their behavior, the thing that will lead to an increase in their productivity. In our applied study, we will try to stand on knowing the reality of the organizational culture in the industrial companies and determine its ability to boost workers productivity through investigating which type of organizational culture has the most impact on the workers’ productivity in the company sampled; mainly due to the importance of the latter for the continuity and thriving of the company.